Euro area fiscal policies and the crisis - Ad van Riet (European Central Bank (ECB), 2010)
In mid-September 2008, a global financial crisis erupted which was followed by the most serious worldwide economic recession for decades. As in many other regions of the world, governments in the euro area stepped in with a wide range of emergency measures to stabilise the financial sector and to cushion the negative consequences for their economies. This paper examines how and to what extent these crisis-related interventions, as well as the fall-out from the recession, have had an impact on fiscal positions and endangered the longer-term sustainability of public finances in the euro area and its member countries. The paper also discusses the appropriate design of fiscal exit and consolidation strategies in the context of the Stability and Growth Pact to ensure a rapid return to sound and sustainable budget positions. Finally, it reviews some early lessons from the crisis for the future conduct of fiscal policies in the euro area.
Keywords: E5; E2; 330; financial crisis; financial markets; Fiscal policies; Fiscal Stimulus; SGP; sustainability